2014
DOI: 10.1186/1477-7827-12-2
|View full text |Cite
|
Sign up to set email alerts
|

Leucine-rich diet supplementation modulates foetal muscle protein metabolism impaired by Walker-256 tumour

Abstract: BackgroundCancer-cachexia induces a variety of metabolic disorders of protein turnover and is more pronounced when associated with pregnancy. Tumour-bearing pregnant rats have impaired protein balance, which decreases protein synthesis and increases muscle breakdown. Because branched-chain amino acids, especially leucine, stimulate protein synthesis, we investigated the effect of a leucine-rich diet on protein metabolism in the foetal gastrocnemius muscles of tumour-bearing pregnant rats.MethodsFoetuses of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 46 publications
6
29
0
3
Order By: Relevance
“…Therefore, we found evidence of the benefits produced by leucine-rich dietary supplementation, not only in the placental tissue but also in the fetus: fetal weight was higher in the LMAC group and fetal resorption was lower in the LMAC compared to the MAC group, in agreement with our previous data [19,33]. According to these data, the placenta cell-signaling pathway was unchanged by the leucine-rich diet even in the LMAC group compared to the C and L groups.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, we found evidence of the benefits produced by leucine-rich dietary supplementation, not only in the placental tissue but also in the fetus: fetal weight was higher in the LMAC group and fetal resorption was lower in the LMAC compared to the MAC group, in agreement with our previous data [19,33]. According to these data, the placenta cell-signaling pathway was unchanged by the leucine-rich diet even in the LMAC group compared to the C and L groups.…”
Section: Discussionsupporting
confidence: 93%
“…As observed in our previous reports and in those from other researchers, the ubiquitinproteasome pathway in skeletal muscle is activated during cancer evolution, decreasing the protein content in response to the elevated release of tyrosine relative to the increased expression of 20S and other proteasomal subunits, ultimately leading to protein degradation [19,23,50,53,54]. Likewise, in response to tumor growth, the placental tissues had a higher protein expression of the 20S and 19S subunits, in line with an increase of protein catabolism.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Our previous work showed some important impairments in skeletal muscle in tumour‐bearing rats, which had increased chymotrypsin activity, representing enhancements of the ubiquitin–proteasome pathway . The present results likely suggest that the higher proteolytic activity (increased chymotrypsin activity) that is associated with higher cell activity (higher AP activity) in heart tissue could be responsible for the ECG failure that was observed only in group W. In our previous research, as also found here, the leucine‐rich diet also minimized the observed changes in those enzymes, even in the heart.…”
Section: Discussionsupporting
confidence: 82%
“…One of these strategies is nutritional supplementation with leucine, which is a branched‐chain amino acid (BCAA) that plays an important role in skeletal muscle metabolism [16]. Leucine efficiently improves skeletal muscle protein synthesis in patients [17, 18] and in animals, as shown previously [1922]. Leucine alone and in a complete BCAA mixture stimulates protein synthesis and decreases protein proteolysis [2325].…”
Section: Introductionsupporting
confidence: 60%